Fabrication of an electrochemical sensor based on gold nanoparticles/carbon nanotubes as nanocomposite materials: determination of myricetin in some drinks - Hajian, Reza; Yusof, Nor Azah; Faragi, Tayebe; Shams, Nafiseh (Public Library of Science, 2014)
In this paper, the electrochemical behavior of myricetin on a gold nanoparticle/ethylenediamine/multi-walled carbon-nanotube modified glassy carbon electrode (AuNPs/en/MWCNTs/GCE) has been investigated. Myricetin effectively accumulated on the AuNPs/en/MWCNTs/GCE and caused a pair of irreversible redox peaks at around 0.408 V and 0.191 V (vs. Ag/AgCl) in 0.1 mol L−1 phosphate buffer solution (pH 3.5) for oxidation and reduction reactions respectively. The heights of the redox peaks were significantly higher on AuNPs/en/MWNTs/GCE compare with MWCNTs/GC and there was no peak on bare GC. The electron-transfer reaction for myricetin on the surface of electrochemical sensor was controlled by adsorption. Some parameters including pH, accumulation potential, accumulation time and scan rate have been optimized. Under the optimum conditions, anodic peak current was proportional to myricetin concentration in the dynamic range of 5.0×10−8 to 4.0×10−5 mol L−1 with the detection limit of 1.2×10−8 mol L−1. The proposed method was successfully used for the determination of myricetin content in tea and fruit juices.